Sistema para gestión de la calidad del caso: Asociación de Confecciones "ARITA", dedicada a la producción y comercialización de productos textiles promocionales, ubicado en el barrio Santa Ana de Chillogallo al sur de Quito, en el año 2014 - Alcocer Ambuludi, Mónica del Rocío (2015)
The following research seeks breeding purposes in production processes, is why a Quality Management System being based on the principles and bases of designing ISO 9001: 2008, it is necessary to specify that no certification will take place. In Chapter 1 of this research plan aspects of the conceptual design of the research focused on determining the problem and its definition, objectives of the research both general and specific, the reason and justification for having raised verified the research plan aimed at determining a Quality Management System for the Association garment "Arita" noting applied methodology and framework. In Chapter 2 a rigorous situational analysis is performed on whole Association of Apparel "Arita" to determine the problems that affect the performance and productivity In chapter 3 the theoretical framework of the terms of reference that will serve as support for the implementation of the management system for quality garment Association "Arita" is developed In chapter 4, the proposed structure of the management system for quality based on strategic planning, restructuring processes, delegation of responsibility, quality indicators for making decisions for continuous improvement of the organization develops enabling it to grow and be more competitive in the market. In final conclusions and recommendations that may offer new Quality Management System develops its possible implementation.